Comparison between Different Prescription Methods for Aerobic Training in Young Adults - Policarpo, Fernando; Valdivia-Moral, Pedro; Socorro Luna-Cruz, Maria do; Véliz-Burgos, Alex; Mansilla-Sepúlveda, Juan; Estay-Sepúlveda, Juan Guillermo
Anaerobic threshold and respiratory compensation are used to determine the intensity of aerobic exercise. This study aims to compare heart rate values relative to the percentages of 50%, 60%, 70%, and 80%, a comparison calculated through the reserve heart rate (HRR) and reserve oxygen consumption (VO2R) equations corresponding to the oxygen consumption obtained by the direct method. The sample was composed of 11 men and 10 women: mean age, 21.4 ± 2.8 years. Volunteers performed a maximal treadmill test in which oxygen uptake was measured using the VO2000® metabolic analyzer. The mean body fat percentage was 15.68 ± 8.02% corresponding to a lean body mass of 54.8 ± 13.0 kg and a maximal oxygen uptake (VO2max) of 56.0 ± 8.4 mL/Kg·min−1 . The measured intensities (50%, 60%, 70% and 80% of VO2max) presented significant differences (p < 0.05) for each reference value. Mean values calculated by the HRR equation demonstrated a tendency to underestimate the intensities, while the values calculated by the VO2R equation showed a tendency to overestimate the intensities. As the main conclusion, it is pointed out that both methods were effective for determining the intensity of aerobic training. However, they presented significant differences, and the equations should be adjusted to increase precision. Thus, the use of HRR is recommended for the determination of training intensities